Penerapan Sanksi Pidana Oleh Hakim Terhadap Pelaku Tindak Pidana Kecelakaan Lalu Lintas Yang Mengakibatkan Kematian - Eka Suryani; Nelvitia Purba (Mahkamah : Jurnal Riset Ilmu Hukum, 2024)
Traffic accidents are a very serious health problem in the world which causes death and is ranked 9th in the world. Indonesia is ranked 5th in the world as the country with the highest traffic accident rate. This research aims to determine the application of criminal sanctions by judges to perpetrators of criminal traffic accidents that result in death. The location for data collection in this research is at the Deli Serdang Police Traffic Unit Gakkum Unit which is located on Jl. Sudirman, No. 18. Lubuk Pakam, North Sumatra, Indonesia. The type of research used in this research is empirical research, namely legal research carried out by examining library materials or secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials. These materials are arranged systematically, studied, then a conclusion is drawn in relation to the problem being studied. The data analysis technique used in this legal research uses qualitative analysis. Based on the results of research conducted by Government Regulation no. 37 of 2017 also strengthens the importance of supervision and law enforcement in the field of traffic safety, underlining the need for traffic engineering and improved traffic management to prevent accidents. The research concludes that legal regulations are adequate, but their implementation in the field still requires strengthening, especially in consistently enforcing criminal sanctions. In decision 1271/Pid.Sus/2022/PN/Lbp, there are a number of important factors which are the judge's main considerations in imposing criminal sanctions on perpetrators of traffic accidents that cause death. First, the defendant's negligence factor is the main key in determining sanctions. The judge considered that the defendant's negligence, who was driving the vehicle while tired and sleepy, was the main cause of the accident. Crimes related to traffic accidents also refer to Articles 359 and 360 of the Criminal Code for cases involving death or injury due to negligence. Obligations for public transport companies involved in accidents are also regulated in the LLAJ Law, which includes the obligation to compensate passengers or goods owners. The implementation of this law shows that even though the rules have been stipulated in detail, the effectiveness of law enforcement is still influenced by law enforcement facilities and infrastructure as well as community behavior in complying with applicable rules. It can be concluded that the Criminal Code (KUHP) and Law no. 22 of 2009 concerning Road Traffic and Transportation has provided a clear legal basis. Article 359 of the Criminal Code regulates negligence that results in the death of another person with the threat of a prison sentence of up to five years. In decision 1271/Pid.Sus/2022/PN/Lbp, there are a number of important factors which are the judge's main considerations in imposing criminal sanctions on perpetrators of traffic accidents that cause death. In its application the judge imposed a lighter sentence compared to the maximum sentence regulated in Article 310 paragraph (4) of the Traffic Law, although he still took into account the serious consequences of the defendant's negligence which caused the fatal accident.